Investigating multi-leaf collimator tracking in stereotactic arrhythmic radioablation (STAR) treatments for atrial fibrillation. (28th September 2018) - Lydiard, Suzanne; Caillet, Vincent; Ipsen, Svenja; O'Brien, Ricky; Blanck, Oliver; Poulsen, Per Rugaard; Booth, Jeremy; Keall, Paul
Abstract: Stereotactic arrhythmia radioablation (STAR) is an emerging treatment option for atrial fibrillation (AF). However, it faces possibly the most challenging motion compensation scenario: both respiratory and cardiac motion. Multi-leaf collimator (MLC) tracking is clinically used for lung cancer treatments but its capabilities with intracardiac targets is unknown. We report the first experimental results of MLC tracking for intracardiac targets. Five AF STAR plans of varying complexity were created. All delivered 5  ×  10 Gy to both pulmonary vein antra. Three healthy human target motion trajectories were acquired with ultrasound and programmed into a motion platform. Plans were delivered with a linac to a dosimeter placed on the motion platform. For each motion trace, each plan was delivered with no MLC tracking and with MLC tracking with and without motion prediction. Dosimetric accuracy was assessed with γ -tests and dose metrics. MLC tracking improved the dosimetric accuracy in all measurements compared to non-tracking experiments. The average 2%/2 mm γ -failure rate was improved from 13.1% with no MLC tracking to 5.9% with MLC tracking ( p   <  0.001) and 7.2% with MLC tracking and no motion prediction ( p   <  0.001). MLC tracking significantly improved the consistency between planned and delivered target dose coverage. The 95% target coverage with the prescription dose (V100) was improved from 60% of deliveries with no MLC tracking to 80% of deliveries with MLC tracking ( p   =  0.03). MLC tracking was successfully implemented for the first time for intracardiac motion compensation. MLC tracking provided significant dosimetric accuracy improvements in AF STAR experiments, even with challenging cardiac and respiratory-induced target motion and complex treatment plans. These results warrant further investigation and optimisation of MLC tracking for intracardiac target motion compensation.